Quantitative Magnetic Resonance Imaging of Cortical and Trabecular Bone - Jerban, Saeed; Ma, Yajun; Wei, Zhao; Jang, Hyungseok; Chang, Eric Y.; Du, Jiang (Seminars in Musculoskeletal Radiology, 2020)
Bone is a composite material consisting of mineral, organic matrix, and water. Water in bone can be categorized as bound water (BW), which is bound to bone mineral and organic matrix, or as pore water (PW), which resides in Haversian canals as well as in lacunae and canaliculi. Bone is generally classified into two types: cortical bone and trabecular bone. Cortical bone is much denser than trabecular bone that is surrounded by marrow and fat. Magnetic resonance (MR) imaging has been increasingly used for noninvasive assessment of both cortical bone and trabecular bone. Bone typically appears as a signal void with conventional MR sequences because of its short T2*. Ultrashort echo time (UTE) sequences with echo times 100 to 1,000 times shorter than those of conventional sequences allow direct imaging of BW and PW in bone. This article summarizes several quantitative MR techniques recently developed for bone evaluation. Specifically, we discuss the use of UTE and adiabatic inversion recovery prepared UTE sequences to quantify BW and PW, UTE magnetization transfer sequences to quantify collagen backbone protons, UTE quantitative susceptibility mapping sequences to assess bone mineral, and conventional sequences for high-resolution imaging of PW as well as the evaluation of trabecular bone architecture.
Keywords: cortical bone; trabecular bone; ultrashort echo time; bound water; pore water; collagen